Quasi‐simultaneous Mapping of Local Current Density, pH and Dissolved O2. Issue 12 (14th July 2015) - Taryba, Maryna G.; Montemor, M. F.; Lamaka, S. V.
Abstract: For the first time we report on quasi‐simultaneous mapping of local current density, pH and concentration of dissolved O2 . The three micro‐probes were positioned 50 micron apart from each other and 50 to 100 µm above the cut‐edge metal coated steel sample. The vibrating probe recorded the local current density and glass‐capillary micro‐electrode measured local pH. Additionally, two different micro‐probes were used for DO measurements: either an amperometric micro‐probe or micro‐optode was coupled with the other two sensors using the triple head stage. The data on local distributions were acquired quasi‐simultaneously (within ≤ 2.8 s) and, hence, are correlated in space and time. Abstract :